An equivalent simulation modeling method for medium-frequency GFW full-power converter wind turbines - LU Yi; WU Wenbo; GU Yilei; XU Feng; YE Wenyao; ZHANG Zheren; XU Zheng (Zhejiang dianli)
Electromagnetic transient （EMT） simulation modeling of medium-frequency grid-following （GFW） wind turbines is fundamental for the design and dynamic characteristic analysis of wind power integration systems. This paper proposes an equivalent simulation modeling method for wind turbines based on controlled voltage and current sources. First， the fundamental circuit structure and control system principles of medium-frequency GFW wind turbines are introduced. Subsequently， an equivalent model framework for the wind turbines is proposed， and the detailed structures of the main circuit， controller， and interface are rigorously derived. Finally， a simulation model of the medium-frequency wind turbine integrated into the grid is developed in PSCAD/EMTDC. Comparative simulations between the detailed model and the proposed equivalent model validate the effectiveness and computational efficiency of the method.